Smart Governance Dalam Kebijakan Perencanaan Dan Penganggaran Di Badan Perencanaan Pembangunan Daerah (Bappeda) Kota Makassar - Muhajir, Rahmat; Nasrulhaq, Nasrulhaq; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACKThis research study  to determine the implementation of Smart Governance in policies, bureaucracy, and services at the Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Makassar. This research uses qualitative research with descriptive type. There  were four informants in this study. The research data were collected through observation, interviews, and documentation. Validation of data is done through triangulation of sources, techniques, and the past time is analyzed through data collection techniques, data reduction, data presentation and conclusion drawing. The results of the study show that the implementation of Smart Governance in the Makassar City BAPPEDA from the bureaucratic aspect has been running effectively and efficiently with orientation to the principle of Smart Governance, namely digitalization. Meanwhile, from the aspect of services, transparency and accountability have been carried out, seen from the services carried out by the Makassar City Bappeda, the mechanism starts from the Kelurahan, Kecamatan, and OPD forums. Meanwhile, from a policy perspective, the participatory principle is still not good. A fairer improvement is needed without taking sides with certain groups.Keywords: Policy, Smart Governance